The Effect of Anatomically Forwarded Head Position on Temporomandibular Dysfunction - Mahro Vojdani; Kianoosh Torabi; Alireza Mahmoodi (Isfahan University of Medical Sciences, 2009)
Introduction: A wide range of factors are said to either cause or aggravate temporomandibular dysfunction (TMD).Some are however under controversy. One such controversial factor is the forward head position. The aim of this study was to compare head positioning between cases of TMD and normal population.Materials and Methods: In this experimental-clinical study, 45 females and 38 males with TMD were divided into two groups as mild-moderate and severe based on Helkomo index. The control group consisted of 30 females and 24 males without any sign of TMD. The angle between the line connecting ear tragus to the spinous process of C7 and the horizontal plate was measured in three successive days and three times in every visit using a goniometer. Then the means were calculated and the collected data were analyzed using one-way ANOVA and t-test.Results: The difference between subjects in the control and the case group with and without sex differentiation was statistically significant (P <0.001).Yet the difference between cases of mild-medium group and severe group both with and without sex differentiation was not statistically significant (P >0.05).The difference between males and females in the control group was not significant either (P =0.223).Conclusion: Both females and males in the case group showed a more forward head position compared to females and males in the control group. Therefore, the subjects suffering from TMD seem to have a more forwarded head position than normal population. Moreover sex and TMD severity are not apparently effective on forwarded head position.